Coexistence of blaOXA-48 and Truncated blaNDM-1 on Different Plasmids in a Klebsiella pneumoniae Isolate in China - Xie, Lianyan; Dou, Yi; Zhou, Kaixin; Chen, Yue; Han, Lizhong; Guo, Xiaokui; Sun, Jingyong (Frontiers in Microbiology, 2017)
Objectives: To describe the genetic environment, transferability, and antibiotic susceptibility of one clinical Klebsiella pneumoniae isolate harboring both blaOXA-48 and blaNDM-1 on different plasmids from a Chinese hospital. Methods: The isolate was subjected to antimicrobial susceptibility testing and multilocus sequence typing using Etest and PCR. The plasmids harboring blaOXA-48 and blaNDM-1 were analyzed through conjugation experiments, S1-nuclease pulsed-field gel electrophoresis, and hybridization with specific probes. Plasmid DNA was sequenced using Pacbio RS II and annotated using RAST. Results: K. pneumoniae RJ119, carrying both blaOXA-48 and blaNDM-1, was resistant to almost all carbapenems, cephalosporins, fluoroquinolone, and aminoglycosides and belonged to ST307. blaOXA-48 was located on a 61,748-bp IncL/M conjugative plasmid, which displayed overall nucleotide identity (99%) to pKPN-E1-Nr.7. blaNDM-1 was located on a 335,317-bp conjugative plasmid, which was a fusion of a blaNDM-1-harboring InA/C plasmid pNDM-US (140,825 bp, 99% identity) and an IncFIB plasmid pKPN-c22 (178,563 bp, 99% identity). The transconjugant RJ119-1 harboring blaNDM-1 was susceptible to carbapenem, and there was an insertion of IS10 into the blaNDM-1 gene. Conclusions: This is the first report of the coexistence of blaOXA-48 and blaNDM-1 in one K. pneumoniae clinical isolate in China. OXA-48 in RJ119 contributed to the majority to its high resistance to carbapenems, whereas NDM-1 remained unexpressed, most likely due to the insertion of IS10. Our results provide new insight for the relationship between genetic diagnosis and clinical treatment. They also indicate that increased surveillance of blaOXA-48 is urgently needed in China.